MINERALOGICAL COMPOSITION OF THE PRODUCTIVE STRATA OF ZHEZHELIVSKOE KAOLINE DEPOSIT - PRYKHODKO, V.; SHEVCHENKO, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
This article discussed problems of mineralogical composition of kaoline deposits from different source rocks. Zonality of weathering crust and peculiarities of alteration by newly-formed primary minerals have been analyzed.